DEVELOPMENT OF MATHEMATICS LEARNING MEDIA ON GEOMETRY MATERIAL TO INCREASE STUDENTS' INTEREST IN LEARNING - Nadirah, Aisyah; Pertiwi, Amirah Nada; Kasari, Mevi; Sapitri, Nadia Bela; Susanti, Elsa; Zulkardi, Zulkardi; Meryansumayeka, Meryansumayeka (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2024)
This study departs from the difficulty of students in mastering geometry material and the results of the needs analysis on students who expect the presence of learning media that contain elements of games such as the game congklak This type of research is R & D with the ADDIE development model consisting of 5 stages namely analysis, design, development, implementation, and evaluation. Descriptive analysis is used to describe the results of CoMath media development using ADDIE development stages. The results of the material expert validation showed that the comath media obtained a percentage of 80% which was in the very valid category. While the results of media expert validation obtained a percentage of 74,55% which included the valid category. To assess the practicality of teaching aids seen from the results of the assessment of comath media from teachers and students. The percentage obtained from the teacher's assessment is 84.83% and the percentage of student assessment is 80%, both of which are in the very practical category. To see the effectiveness, it was analyzed from the results of observations during the trial and supported by the results of interviews with two VIII grade students. From the analysis, it can be concluded that the comath media developed is valid, effective, and practical